On the Relationship between Low Latitude Scintillation Onset and Sunset Terminator over Africa - Mogese Wassaie Mersha; Elias Lewi; Norbert Jakowski; Volker Wilken; Jens Berdermann; Martin Kriegel (Remote Sensing, 2021)
The solar terminator is a moving boundary between day-side and night-side regions on the Earth, which is a substantial source of perturbations in the ionosphere. In the vicinity of the solar terminator, essential parameters like <semantics>S4</semantics> index measurements are widely analyzed in order to monitor and predict perturbations in the ionosphere. The utilization of the scintillation index <semantics>S4</semantics> is a well-accepted approach to describe the amplitude/intensity fluctuation of a received signal, predominantly caused by small-scale irregularities of the ionospheric plasma. We report on the longitudinal daily and seasonal occurrence of GNSS signal scintillations, using the data derived from the GNSS stations in Bahir Dar, Ethiopia, Lomé, Togo and Dakar, Senegal. The observed seasonal climatology of GNSS signal scintillations in equatorial Africa is adequately explained by the alignment of the solar terminator and local geomagnetic declination line. It should be pointed out that the strongest scintillations are most frequently observed during the time when the solar terminator is best aligned with the geomagnetic declination line. At all three stations, the comparison of computational and observational results indicated that the scintillation activity culminated around equinoxes in the years 2014, 2015 and 2016. Comparatively, the western equatorial Africa sector has the most intense, longest-lasting, and highest scintillation occurrence rate in equinoctial seasons in all three years. For the first time, we show that the seasonal variation of the scintillation peaks changes systematically from west to east at equatorial GNSS stations over Africa. A detailed analysis of the solar day–night terminator azimuth at ionospheric heights including the time equation shows that the scintillation intensity has a maximum if the azimuth of the terminator coincides with the declination line of the geomagnetic field. Due to the remarkable change of the declination by about 10° at the considered GNSS stations, the distance between scintillation peaks increases by 46 days when moving westward from the Bahir Dar to the Dakar GNSS station. The observations agree quite well with the computational results, thus confirming Tsunoda’s theory.